A DNA Circuit for IsomiR Detection. (14th October 2016) - Connolly, Ashley R.; Hirani, Rena; Ellis, Amanda V.; Trau, Matt
Abstract: A synthetic DNA oligonucleotide has been programmed to function as a biological circuit to detect 5′‐IsomiRs. The circuit consists of two integrated DNA switches. The first is "activated" when a DNA probe is enzymatically modified by a reverse transcriptase that incorporates nucleotides complementary to the 5′‐region of a microRNA (miRNA). Addition of the correct number and sequence of nucleotides enables the probe to assemble into an asymmetric DNA hairpin. The reconfigured hairpin probe then primes an internal polymerisation reaction, resulting in the synthesis of a symmetrical DNA hairpin. This activates the second switch, which then initiates the amplification of reverse‐transcribed miRNA through a continuous cycle of DNA nicking and polymerisation. The DNA circuit enables sensitive and rapid detection of femtomoles of a miRNA transcript under isothermal conditions. Abstract : An oligonucleotide was designed to function as a DNA circuit to detect IsomiRs. The circuit consists of two DNA switches. The first is "activated" by reverse transcription of a microRNA. Nucleotides complementary to the 5′‐region of the microRNA promote DNA hairpin formation. This "activates" the second switch, which initiates DNA amplification.